The chorus of drama in the fourth century BCE presence and representation - Jackson, Lucy 1986- (Oxford classical monographs, 2020)
This comprehensive study of the ancient Greek dramatic chorus in the fourth century reassesses the traditional narrative that it more or less 'declined' in quantity and quality, demonstrating instead how varied and vital this component of drama continued to be during a time when the theatre became truly international